Evidence for a Role of CCR6+ T Cells in Chronic Thromboembolic Pulmonary Hypertension - van Uden, Denise; Koudstaal, Thomas; van Hulst, Jennifer A. C.; van den Bosch, Thierry P. P.; Vink, Madelief; Bergen, Ingrid M.; Lila, Karishma A.; van den Bosch, Annemien E.; Bresser, Paul; Kool, Mirjam; von der Thüsen, Jan H.; Hendriks, Rudi W.; et al. (Frontiers in Immunology, 2022)
Introduction Previous studies have shown an increase of T cells and chemokines in vascular lesions of patients with chronic thromboembolic pulmonary hypertension (CTEPH). However, detailed characterization of these T cells is still lacking, nor have treatment effects been evaluated. Methods We included 41 treatment-naive CTEPH patients at diagnosis, 22 patients at 1-year follow-up, and 17 healthy controls (HCs). Peripheral blood T cells were characterized by flow cytometry for subset distribution, cytokine expression and activation marker profile. We used multiplex immunofluorescence to identify CCR6+ T cells in endarterectomy tissue from 25 patients. Results At diagnosis, proportions of CCR6+ CD4+ T cells were increased in CTEPH patients compared with HCs. Patients displayed a significantly reduced production capacity of several cytokines including TNFα, IFNγ, GM-CSF and IL-4 in CD4+ T cells, and TNFα and IFNγ in CD8+ T cells. CD4+ and CD8+ T cells showed increased expression of the immune checkpoint protein CTLA4. Multivariate analysis separated CTEPH patients from HCs, based on CCR6 and CTLA4 expression. At 1-year follow-up, proportions of CCR6+CD4+ T cells were further increased, IFNγ and IL-17 production capacity of CD4+ T cells was restored. In nearly all vascular lesions we found substantial numbers of CCR6+ T cells. Conclusion The observed increase of CCR6+ T cells and modulation of the IFNγ and IL-17 production capacity of circulating CD4+ T cells at diagnosis and 1-year follow-up – together with the presence of CCR6+ T cells in vascular lesions - support the involvement of the Th17-associated CCR6+ T cell subset in CTEPH.